2014
DOI: 10.1021/nl5028638
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 Transistors Operating at Gigahertz Frequencies

Abstract: The presence of a direct band gap and an ultrathin form factor has caused a considerable interest in two-dimensional (2D) semiconductors from the transition metal dichalcogenides (TMD) family with molybdenum disulfide (MoS2) being the most studied representative of this family of materials. While diverse electronic elements, logic circuits, and optoelectronic devices have been demonstrated using ultrathin MoS2, very little is known about their performance at high frequencies where commercial devices are expect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 39 publications
1
141
0
Order By: Relevance
“…High-frequency operation of MoS 2 FETs was also recently demonstrated by Krasnozhon et al (Figure 4), who demonstrated current, voltage, and power gains in the gigahertz range in transistors based on 1−3 layer thick MoS 2 with a channel length of 240 nm. 16 This shows that the mobility of MoS 2 is large enough to allow device operation in the technologically relevant gigahertz frequency range. These performance figures are currently limited rather by the contact resistance and relatively large gate lengths, and scaling is expected to result in further improvements of the operating speed.…”
Section: ■ Mos 2 Transistorsmentioning
confidence: 93%
“…High-frequency operation of MoS 2 FETs was also recently demonstrated by Krasnozhon et al (Figure 4), who demonstrated current, voltage, and power gains in the gigahertz range in transistors based on 1−3 layer thick MoS 2 with a channel length of 240 nm. 16 This shows that the mobility of MoS 2 is large enough to allow device operation in the technologically relevant gigahertz frequency range. These performance figures are currently limited rather by the contact resistance and relatively large gate lengths, and scaling is expected to result in further improvements of the operating speed.…”
Section: ■ Mos 2 Transistorsmentioning
confidence: 93%
“…3(a) inset]. With low resistance Ohmic contacts to the MoSe 2 monolayer, it should be possible to exploit the strong V g dependence of excitonic response to realize fast switching of mirror transmission and reflection, potentially on subnanosecond time scales [24].…”
Section: (C)mentioning
confidence: 99%
“…3 While the RF applications of MoS 2 are still in their infancy, recent studies have pushed exfoliated MoS 2 cut off frequencies significantly higher. [4][5][6] The study by Krasnozhon et al employed edge contacts to achieve an intrinsic f T of 25 GHz in trilayer exfoliated MoS 2 . 5 The work by Cheng et al used transferred gate stacks on multilayer exfoliated MoS 2 to obtain an intrinsic f T of 42 GHz.…”
Section: Molybdenum Disulfide (Mosmentioning
confidence: 99%